Glass Dielectrics in Extreme High‐Temperature Environment. Issue 12 (12th September 2016) - Gao, Jun; Kwon, Do‐Kyun; Perini, Steven; Long, Jeffery; Zhang, Shihai; Lanagan, Michael T.
Abstract : Thin and flexible glass ribbons can be rolled into a film capacitor structures for power electronic circuits. Glass has excellent electrical properties and is a leading candidate to replace polymer films for high‐temperature applications. The dielectric properties of a low‐alkali aluminoborosilicate glass were characterized up to temperatures of 400°C. Low‐field permittivity values of 6 with dielectric loss below 0.01 were found for temperatures below 300°C. The dielectric breakdown strength exceeded 5 MV/cm for temperature of 400°C and high‐field polarization measurements showed that glass has over 95% energy efficiency at temperatures of 200°C, which is a target temperature for high‐temperature power electronic circuits driven by wide bandgap semiconductor devices.